Analisis Peran Guru dalam Menciptakan Lingkungan Belajar Kondusif di Madrasah Aliyah NW Kabar - Abdul Latif; Nila Lailatul Fitri; Hilmi Najamuddin; Gina Ilhami Fatin; Sefty Cahyaningtyas; Ewit Nurdayanti; Teti Hifsatun Aini; Muhammat Riyandi; M. Sastra Budiyawan (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to examine how teachers help students learn effectively at MA NW Kabar. When students feel supported and encouraged in their learning, they are more likely to be motivated and perform well (Sardiman, 2020). The study used a learning method that emphasizes detailed understanding, where data was collected through observation, talking with people, and reviewing documents (Sugiyono, 2022). Teachers help students feel comfortable, safe, and engaged in learning. Teachers do more than just teach. They also help students learn, encourage them, and show them how to behave. Strategies used include effective communication, the application of a humanistic approach, and creative and disciplined classroom management (Mulyasa, 2021). In conclusion, the role of teachers in creating a conducive learning environment is crucial to the success of the educational process and the development of student character